Non-resonant acceleration of charged particles driven by the associated effects of the radiation reaction. (October 2020) - Russman, F.; Almansa, I.; Peter, E.; Marini, S.; Rizzato, F. B.
Abstract : In the present analysis, we study effects of the radiation reaction (RR) on the dynamics of charged particles submitted to the action of localized longitudinal high-frequency carriers travelling at the speed of light. As the wave's crests and troughs keep overtaking particles, dissipative RR forces tend to drag particles alongside the wave in an effort to reduce the relative wave–particle speed. Particles of course never reach the phase velocity of the wave, but are instead driven to an ever-growing velocity, towards the speed of light, while in the wave localization region. We developed a modified average Hamiltonian formalism capable of describing the intricacies of the corresponding dynamics. The modified formalism agrees with simulations and is of particular usefulness in the study of optimum values for the localization length and maximum wave amplitude.